2017
DOI: 10.1038/s41598-017-06485-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive detection of cross-sectional strain and defect structure in an individual Ag five-fold twinned nanowire by 3D electron diffraction mapping

Abstract: Coherent x-ray diffraction investigations on Ag five-fold twinned nanowires (FTNWs) have drawn controversial conclusions concerning whether the intrinsic 7.35° angular gap could be compensated homogeneously through phase transformation or inhomogeneously by forming disclination strain field. In those studies, the x-ray techniques only provided an ensemble average of the structural information from all the Ag nanowires. Here, using three-dimensional (3D) electron diffraction mapping approach, we non-destructive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Theoretical calculations of clean surface energies (γ) associated with the low-index crystallographic facets of a face-centered cubic metal follow the sequence of γ{111} < γ{100} < γ{110}, , making the highest surface {110} a favorable etching site compared to the more stable {100} and {111}. Although the five internal segments are equivalent, the actual chemical environment can be different, such as defect structures and the internal strain in each single crystalline segment being uneven, which can influence the etching progression.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations of clean surface energies (γ) associated with the low-index crystallographic facets of a face-centered cubic metal follow the sequence of γ{111} < γ{100} < γ{110}, , making the highest surface {110} a favorable etching site compared to the more stable {100} and {111}. Although the five internal segments are equivalent, the actual chemical environment can be different, such as defect structures and the internal strain in each single crystalline segment being uneven, which can influence the etching progression.…”
Section: Resultsmentioning
confidence: 99%
“…In other cases, XRD has been used to investigate more complex parameters, providing deeper insights into structural properties. 30–33 For instance, Niu et al 34 used synchrotron XRD to characterize newly synthesized AgNWs and underscored the significant asymmetry in most peaks, attributed to an apparent secondary peak with a slightly different interplanar spacing. They concluded that highly inhomogeneous strains exist in different directions within each AgNW five-fold section, likely due to the folded conformation itself.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that highly inhomogeneous strains exist in different directions within each AgNW five-fold section, likely due to the folded conformation itself. Fu et al , 33 applying a 3D electron diffraction mapping approach, demonstrated that the five single crystallites in individual AgNWs have inhomogeneous strain distribution. This difference comes from internal strain energy relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the experimental studies on the strain-relaxation phenomena and the related mechanism of five-fold twinned structures were almost focus on the metallic objects. [15][16][17][18][19][20] In comparison, limited experimental investigations revealed the defect structures for the elastic strain relaxation in covalent five-fold twinned structures. [14,[21][22][23][24] In this work, the strain-relieving defects have been non-destructively revealed in two types of five-fold twinned nanowires (FTNWs) using 3D electron diffraction mapping methodology.…”
Section: Introductionmentioning
confidence: 99%
“…One is a pentagonal Ag nanowire with diameter of 55 nm and the other is a star-shaped B 4 C nanowire with diameter of 92 nm, both of them have basically equal twin-plane width in the radial direction. The 3D electron diffraction mapping methodology allows to obtain the 3D intensity distribution of specific reflections diffracted from nanostructures [18,21] in a relatively small tilting range compared with real-space electron tomography. [25] Traditionally, the transverse structural observation of one-dimensional (1D) nanostructures in transmission electron microscope (TEM) required the cross-sectional sample preparation which inevitably introduces external strain or defects interfering the characterization of the intrinsic structures.…”
Section: Introductionmentioning
confidence: 99%